Propuesta Psicopedagógica de ejercicios de estimulación cognitiva para mejorar la atención en un alumno con Trastorno por déficit de atención e hiperactividad (TDAH) del cuarto grado de la escuela de Educación Básica Miguel Riofrío, 2021-2022. - Sarango Sarango, Lorena Margoth (2022)
The present Curricular Integration Work called: Psycho-pedagogical proposal of cognitive stimulation exercises to improve attention in a student with Attention Deficit Hyperactivity Disorder (ADHD) in the fourth grade of the Miguel Riofrío Basic Education School, 2021-2022; The general objective was: To implement the psycho-pedagogical proposal of cognitive stimulation exercises to improve attention in a student with ADHD in the fourth grade of the Miguel Riofrío School of Basic Education, through a qualitative approach methodology, of a descriptive type, with a pre-experimental design, cross-sectional and case study method. The population was a student (boy) of fourth grade of basic education, which was selected by non-probabilistic sampling method. The techniques used were: interviews, psycho-pedagogical sheet, observation sheet, the CONNERS scale for parents and teachers, the d2 attention test and the achievement sheet that served to collect the information. The results obtained from the present investigation determined that teachers maintain a doubtful knowledge in view of the fact that they confuse ADHD with a deficiency. Regarding the characterization of family situations, it was evidenced that the minor comes from a nuclear family and they get along well with each other, there is no violence; in the social part, the child has difficulties relating to his peer group, doing group work and shows attitudes of boredom and frustration; Based on school situations, the student makes frequent mistakes in homework and work due to his inattention, is easily distracted and even fails to finish his academic homework. Likewise, the attention problems determined by the D2 attention test shows that there is a decrease in productivity due to lack of concentration and fatigue and problems in the speed of data processing, following instructions, discrimination of visual stimuli and in the selective attention. However, after the application of the cognitive stimulation exercises, according to the teacher, the child gradually begins to pay attention, becomes less distracted and tries to finish the tasks in a situation that he did not do before, also through the achievements based on the exercises and activities established, it was possible to maintain selective and sustained attention for a longer time, however, it is still in a state of process in activities related to precision, concentration, speed of mental processing as well as inhibitory control . Thus concluding that the psycho-pedagogical proposal did contribute to the improvement of student care in a minimal way, but necessary for their teaching-learning process, which is why it is recommended to work with a population of students who do or do not have some special educational need. associated or not with a disability by virtue of the fact that its benefits are relevant to any area that is intended to work and obtain satisfactory results.